Verdi's La Traviata - Verdi, Giuseppe, 1813-1901.; Fisher, Burton D. (Coral Gables, Fla. : Opera Journeys, 2001)
-- Engaging Commentary and Analysis about the composer, the opera and its characters.-- Story Narrative with Music Highlight Examples-- A complete Libretto (newly translated) that incorporates Music Highlight Examples-- A Discography-- A Videography-- A Dictionary of Opera and Musical TermsEach Opera Classics Library edition is a comprehensive guide and complete analysis and evaluation of a specific opera; each is a unique "encyclopedia" that integrates important and pertinent information about each timeless classic. The objective of Opera Classics Library is to unlock opera's mysteries for the general audience, and enlighten and educate. Understanding and knowledge are the master keys to enhance enjoyment and appreciation of this great art form. Alexandre Dumas, in the final words of his novel, La Dame aux Camelias, dutifully summed up the sense of poignancy that became the basis of one of Verdi's most treasured operas: "Sleep in peace, Marguerite! Much will be forgiven you for you have greatly loved." La Traviata is an intimate portrait of a woman's agonizing defeat against the forces of destiny. Verdi's music score is a tone poem that musically captures the story's profound human passions and psychological depth
Commentary and analysis -- Principal characters in La traviata -- Brief story synopsis -- Story narrative : with music highlight examples -- Libretto : with music highlight examples -- Discography -- Videography -- Dictionary of opera and musical terms.
Discography: pages 91-96.
Videography: pages 97-100.
Print version record.
eBooks on EBSCOhost
Keywords: Verdi, Giuseppe, -- 1813-1901.; Traviata (Verdi, Giuseppe); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos